Association between treatment adherence and personality traits, anxiety and depression among adult patients with HIV in Northwest Peninsular Malaysia - Ming, Ng Ming (2021)
Background: Antiretroviral therapy is a life-saving treatment for HIV-positive individuals. However, to achieve complete viral suppression, they must maintain adherence to treatment every day. Factors affecting adherence to Antiretroviral therapy has been studied by many researchers in Western and Asian countries like Malaysia. However, up until now, there is still a lack of studies focusing on understanding the association between treatment adherence and anxiety, depression, and personality traits among adult HIV patients receiving ART in Malaysia. Objective: To study treatment adherence in adult HIV patients receiving ART and its association with personality traits, anxiety, and depression at Hospital Perlis and Kedah. Method: A hospital-based cross-sectional study was conducted from July 1, 2018, to April 31, 2020, among 229 adult patients under outpatient department HIV clinic follow-up. Participants that fulfilled the criteria were selected via a purposive sampling method. Data were collected through an interviewer-guided questionnaire set. The anxiety and depression were evaluated through the Hospital Anxiety and Depression Scale (HADS), while the personality traits were examined through the Zuckerman-Kuhlman personality test (ZKPQ-M-40-CC). Adherence to ART was assessed through an interviewer-guided Timeline follow-back (TLFB). Sociodemographic, clinical characteristics, mood symptoms, and personality variables were collected. A total of 229 respondents completed HADS, ZKPQ-M-40-CC, and TLFB. Result: There were 220 (96.1%) out of 229 participants who adhered to therapy. Older individuals 167(97.7%) more adhered to treatment as compared with younger individuals 53(91.4%); (p-value=0.033). Those who were married 91(98.9%) were more likely to adhere to treatment than those who were single 107(95.5%) or divorced 25(88.0%); (p-value=0.044). Only 2 (3.2 %) of the 62 participants who had an anxiety disorder did not adhere to therapy; (p-value=0.542). Only 5 (5.0%) of the 100 participants with a depressive disorder did not adhere to therapy; (p-value=0.509). An individual with an Activity type of personality trait more adhered to treatment 30 (±5.8); (p-value=0.014) as compared to an individual with Sociability 24(±5.0); (p-value=0.320), Aggression-Hostile 18(±6.3); (p-value=0.650), Impulsive-Sense-Seeking 18(±6.3); (p-value=0.688), and Neurotic-Anxious 18(±6.3); (p-value=0.623) type of personality traits. Multiple logistic regression found that the activity domain of the personality trait was the only factor significantly associated with ART treatment adherence after controlling for age, education level, and viral load. An increase in one score of the activity domain of the personality trait has a 1.14 (95% CI: 1.02, 1.28) higher odds of being adherent to therapy. Conclusion: The results of this study revealed that there was a direct relationship between Activity personality trait with treatment adherence where higher scores in the Active personality domain predicted higher adherence to treatment. Conversely, anxiety and depression are not associated with adherence to treatment. Personality trait assessment can help in the identification of HIV patients who are at risk for poor adherence especially for those who score low in the activity domain of personality trait. As such by conducting behavioural modification therapy for the vulnerable individual can help to improve and increase their treatment adherence.